Advances and gaps in SARS-CoV-2 infection models. - César Muñoz-Fontela; Lina Widerspick; Randy A Albrecht; Martin Beer; Miles W Carroll; Emmie de Wit; Michael S Diamond; William E Dowling; Simon G P Funnell; Adolfo García-Sastre; Nora M Gerhards; Rineke de Jong; et al. (PLoS Pathogens)
The global response to Coronavirus Disease 2019 (COVID-19) is now facing new challenges such as vaccine inequity and the emergence of SARS-CoV-2 variants of concern (VOCs). Preclinical models of disease, in particular animal models, are essential to investigate VOC pathogenesis, vaccine correlates of protection and postexposure therapies. Here, we provide an update from the World Health Organization (WHO) COVID-19 modeling expert group (WHO-COM) assembled by WHO, regarding advances in preclinical models. In particular, we discuss how animal model research is playing a key role to evaluate VOC virulence, transmission and immune escape, and how animal models are being refined to recapitulate COVID-19 demographic variables such as comorbidities and age.